Effectiveness of cupping therapy for musculoskeletal pain: an umbrella review - Magdy Elmeligie, Mohamed; Yehia, Amr H.; Hamada Mohamed, Mahmoud; Mahmoud, Manna; Alkholui, Mohamed N.; Mohamed, Ghada I. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. This umbrella review aimed to review and synthesise the findings of published systematic reviews and meta-analyses analysing the effects of cupping therapy programs on musculoskeletal pain in athletes and the general population.Methods. A search in PubMed, Web of Science, Scopus, MEDLINE, Cochrane Central, CINAHL, EMBASE, and PEDro was performed. The methodological quality of the included systematic reviews was evaluated using the 16 domains of the AMSTAR2 checklist. Based on the performance in these 16 domains of different weights, an overall rating was generated, and the quality was determined to be critically low (1–4), low (5–8), moderate (9–12), or high (13–16). The overall confidence in the results of the reviews was low. Among the critical items, all reviews failed to present a list of excluded trials, four reviews did not consider the risk of bias when presenting or discussing their results, three reviews did not use adequate methods for the meta-analysis, the impact of publication bias was not investigated in three reviews, and the absence of a planned protocol to guide the review was noted in two reviews. Most reviews included trials of low quality (i.e., high risk of bias).Results. A total of 301 studies involving 27,960 participants were analysed in 21 systematic reviews. The review confirmed that cupping therapy is more effective than passive interventions such as heat therapy, usual care, conventional medications, and no treatment. However, its effectiveness is similar to acupuncture. There is not enough evidence to recommend cupping therapy for athletes, and there are associated risks such as hematoma, pain at the application site, increased pain, tingling sensations, and dizziness.Conclusions. Considering the standards, this umbrella review showed that most systematic reviews and meta-analyses using cupping therapy for musculoskeletal pain present low methodological quality. Most of the systematic reviews in this umbrella revealed that cupping therapy is ineffective in improving musculoskeletal pain in the athletic and general populations.
Keywords: athletes; cupping therapy; pain; musculoskeletal injury; general population